A Study of Cardiogenic Stroke Risk in Non-valvular Atrial Fibrillation Patients - Song, Ziliang; Xu, Kai; Hu, Xiaofeng; Jiang, Weifeng; Wu, Shaohui; Qin, Mu; Liu, Xu (Frontiers in Cardiovascular Medicine, 2020)
Objectives We attempted to develop more precisely quantified risk models for predicting cardiogenic stroke risk in non-valvular atrial fibrillation (NVAF) patients. Methods We conducted a case-control study, using data from hospitalized patients with AF who underwent transesophageal echocardiography at Shanghai Chest Hospital. A total of 233 high cardiogenic stroke risk patients with LAT or LA-SEC and 233 controls matched for age, sex, AF type. Results AF history, LA diameter enlargement, larger left ventricular end diastolic diameter, lower ejection fraction, greater SUA and BNP levels showed association with high stroke risk. The multivariate logistic regression analysis revealed that AF duration, LAd, LVEF, SUA and BNP were independent risk factors of the LAT/LA-SEC. We used LAd, LVEF, SUA and BNP to construct a combined predictive model for high stroke risk in NVAF patients (the area under ROC curve: 0.784; sensitivity 66.1%; specificity 76.8%; 95% CI 0.744–0.825, P<0.001). Conclusion Comprehensive evaluation of LAd, LVEF, SUA and BNP may help stratify the cardiogenic stroke risk among nonvalvular AF patients, and strengthen anticoagulation therapy.